KEBIJAKAN KRIMINAL DALAM MENANGGULANGI UPAYA MAKAR YANG DILAKUKAN OLEH ORGANISASI PAPUA MERDEKA (STUDI KASUS PUTUSAN PENGADILAN NEGERI NOMOR 1304/2019/PID.B.2019/PN JKT PST) - Grace Angelia Soenartho (Fakultas Hukum Universitas Tarumanagara, 2021)
The issue of racism against youth from Papua in Surabaya occurred in 2019, as a result of which the Papuan Youth demanded a referendum and led to acts of treason by raising the Morning Star flag and anti-red and white chants. So the main problem in this study is the form of criminal policy in dealing with acts of treason in Indonesia. The research method is normative law with the aim of writing to analyze criminal policies in tackling the crime of treason in Indonesia. The results of the research in this paper are the Jakarta District Court decided that the defendants fulfilled the elements of the crime of treason according to the Criminal Code, namely the element of every person, the element of treason, the element with the intention that all or part of the country's territory fell into the hands of the enemy and separated part of the country's territory and elements of those who committed, ordered do, participate in doing, then a criminal policy is taken through penal measures for violating Article 87 in conjunction with Article 106 of the Criminal Code. The penalty effort was chosen because the defendant was proven to have committed a crime that threatened the security and integrity of the Republic of Indonesia. The second effort is non-penal as a form of prevention or prevention by instilling Pancasila values, a sense of nationalism, and updating the rules of the Dutch colonial period into the RKUHP so that the existing Criminal Code regulations are more firm and clear. Therefore, institutions authorized to form rules regarding treason, so that the 2019 RKUHP can be discussed critically by taking into account the development of national, global law and the cultural development of society so that it can be well realized in legal justice in Indonesia.